Penemuan Kasus Kusta pada Narakontak Serumah Pasien Kusta dengan Deteksi Kadar Antibodi IgM Anti PGL-1 - Mutia Fadhila Sy; Ramona Dumasari Lubis (MAHESA : Malahayati Health Student Journal, 2026)
ABSTRACT Leprosy is a chronic infectious disease that remains a significant public health concern, particularly in endemic regions. Transmission frequently occurs among household contacts of leprosy patients, especially in the presence of risk factors such as household crowding and compromised immunity. Early detection among household contacts is crucial to prevent ongoing transmission, with anti-PGL-1 IgM antibody serological testing serving as an important diagnostic adjunct. Case Report: We report a case of a 9-year-old boy presenting with non-pruritic hypopigmented patches on both cheeks for six months. The patient had a history of close household contact with his grandmother, who was undergoing multidrug therapy for multibacillary leprosy. Dermatological examination revealed hypopigmented macules with sensory loss, without thickening of peripheral nerves. Slit skin smear and KOH tests were negative. Serological testing showed elevated anti-PGL-1 IgM antibody levels (1593 u/ml; cutoff: 605 u/ml), supporting the diagnosis of paucibacillary leprosy. The patient was started on pediatric MDT-PB and the family was provided with education regarding the disease and its transmission. Neuropathy assessment using the Semmes-Weinstein Monofilament test and the Toronto Clinical Scoring System was within normal limits. Conclusion: Serological testing for anti-PGL-1 IgM antibodies is a valuable adjunct for diagnosing leprosy, particularly in new cases with ambiguous clinical features and among household contacts, enabling early diagnosis and timely management. Keywords: Leprosy, Household Contact, Anti-PGL-1 Igm Antibody, Paucibacillary Leprosy, Early Diagnosis, Child.  ABSTRAK Kusta merupakan penyakit infeksi kronis yang masih menjadi masalah kesehatan masyarakat, terutama di daerah endemis. Penularan sering terjadi pada narakontak serumah dengan pasien kusta, terutama bila terdapat faktor risiko seperti kepadatan hunian dan status imunitas yang rendah. Deteksi dini pada narakontak serumah sangat penting untuk mencegah penularan berlanjut, salah satunya melalui pemeriksaan serologis antibodi IgM anti PGL-1. Laporan Kasus: Dilaporkan seorang anak laki-laki usia 9 tahun dengan keluhan bercak putih pada kedua pipi tanpa rasa gatal selama enam bulan. Pasien merupakan narakontak serumah dari nenek yang sedang menjalani pengobatan kusta tipe multibasiler. Pemeriksaan dermatologis menunjukkan makula hipopigmentasi dengan anestesi, tanpa penebalan saraf tepi. Pemeriksaan slit skin smear dan KOH negatif. Pemeriksaan serologis didapatkan kadar antibodi IgM anti PGL-1 yang tinggi (1593 u/ml; cutoff: 605 u/ml), mendukung diagnosis kusta tipe pausibasiler. Pasien mendapat terapi MDT-PB dosis anak dan edukasi kepada keluarga. Hasil pemeriksaan neuropati dengan tes Semmes-Weinstein Monofilament dan Toronto Clinical Scoring System berada dalam batas normal. Kesimpulan: Pemeriksaan serologis antibodi IgM anti PGL-1 sangat bermanfaat sebagai penunjang diagnosis pada kasus kusta dengan manifestasi klinis tidak khas, terutama pada narakontak serumah, sehingga memungkinkan diagnosis dini dan tata laksana yang tepat waktu.  Kata Kunci: Kusta, Narakontak Serumah, Antibodi Igm Anti-PGL-1, Kusta Pausibasiler, Diagnosis Dini, Anak.